2014
DOI: 10.1155/2014/834132
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of an Internally Passively Pressurized Circulation Control Propeller

Abstract: The purpose of circulation control for fixed wing aircrafts is to increase the lifting force when large lifting forces and/or slow speeds are required, such as at takeoff and landing. Wing flaps and slats are used on almost all fixed-wing aircraft. While effective in increasing lift, they do so with penalty of increasing drag, weight, and control complexity. The goal of this research was to find an alternative way of pumping pressurized air to the trailing edge slot on a UAV propeller. This design called for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
0
0
1
Order By: Relevance
“…As the jet velocity increases, the stagnation point moves forward on the lower trailing edge, inducing an effective camber and thereby increasing circulation around the wing and lift. Coandă effect has been studied by many investigators for cylinders and modified airfoil trailing-edge shapes, particularly by Englar et al [4] and Kweder et al [5]. The pressure force decreases with distance from the jet nozzle exit and eventually equals the inertial force at which point the flow separates from the surface.…”
Section: Coandă Effectmentioning
confidence: 99%
“…As the jet velocity increases, the stagnation point moves forward on the lower trailing edge, inducing an effective camber and thereby increasing circulation around the wing and lift. Coandă effect has been studied by many investigators for cylinders and modified airfoil trailing-edge shapes, particularly by Englar et al [4] and Kweder et al [5]. The pressure force decreases with distance from the jet nozzle exit and eventually equals the inertial force at which point the flow separates from the surface.…”
Section: Coandă Effectmentioning
confidence: 99%
“…The aerofoil's lift coefficient values at an angle of attack of 15° are displayed in Table 1. The table displays the values of CL compared to a case study data by Beyhaghi and Amano [5,6] and the current data at 6 o angle of attack. It is evident from the table that there is a good coincidence between the results.…”
Section: Mesh Of the Full Domainmentioning
confidence: 99%
“…An experimental work was conducted by using a passive propeller slot at Re number 1.6 ×10 6 . The outcomes demonstrated that for one of the finest situations studied, the lift coefficient improved by up to 30%, while a negligible increase in drag was noted, [5,6]. A cambered (asymmetric) aerofoil of the blade of a vertical axis wind turbine, was numerically studied by [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ефективність осьових вентиляторів та компресорів авіаційних газотурбінних двигунів (ГТД) є однією з важливих умов, що визначають їх надійність та рівень безпеки польотів [1]. Нестійкість роботи ступеня осьового вентилятора (ОВ) в системі двигуна є при-чиною зменшення ефективності останнього, а також є причиною інтенсивних коливань тиску робочого тіла в проточній частині ГТД.…”
Section: вступunclassified